Illness perception and cardiovascular health behaviour among persons with ischemic heart disease in Indonesia - Kholid Rosyidi Muhammad Nur (Elsevier, 2018)
Objective: A study was conducted to explore the level of illness perception, the level of cardiovascular health behaviour and the relationship between illness perception and cardiovascular health behaviour among persons with ischemic heart disease (IHD) in a community setting. Method: The participants comprised 235 persons with IHD. The instruments used were as follows: 1) Demographic Data and Health Information, 2) The Brief Illness Perception Questionnaire (Brief IPQ), 3) The Open-ended Questionnaire (OEQ), and 4) The Modified Cardiac Health Behaviour Scale (MCHBS). Findings from the OEQ are used to assess in-depth illness perception and to extend the information obtained from the Brief IPQ. The design of the study was descriptive correlational. The data were analysed using descriptive statistics to present the demographic data and health information. Inferential statistics was used to resolve the relationship between illness perception and cardiovascular health behaviour by using Pearson's Product Moment Correlation. Result: The mean score of illness perception was at a moderate level (M = 43.65, SD = 3.93), whereas the mean score of cardiovascular health behaviour was at a high level (M = 80.29, SD = 5.42). A significant positive relationship existed between illness perception and cardiovascular health behaviour among persons with IHD (r = 0.38, P < 0.01). Conclusion: Persons with higher illness perception showed a positive correlation with higher cardiovascular health behaviour at a significant level of 0.01. Results provided important information for nurses to develop an intervention program to promoting appropriate illness perception and cardiovascular health behaviour among persons with IHD. Keywords: Illness perception, Cardiovascular health behaviour, Ischemic heart disease